1999
DOI: 10.1007/s002340050846
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial dural arteriovenous fistulae with perimedullary venous drainage. Anatomical, clinical and therapeutic considerations

Abstract: We report five cases of intracranial dural arteriovenous fistula (DAVF) with perimedullary venous drainage. All the patients presented with rapidly progressive myelopathy and three had autonomic disorders. The DAVF were on the tentorium cerebelli (two cases), sigmoid (one), superior petrosal (one), and cavernous sinus (one). Slow venous drainage was directed through dilated perimedullary cervical veins. The transverse sinus was occluded in two cases. MRI, performed in four cases, demonstrated high signal on T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 18 publications
2
49
0
3
Order By: Relevance
“…To the best of our knowledge, only one case has been reported for the bridging venous drainage in the English literature [6]. Although we found some additional cases of angiography suggesting bridging venous drainage to the APM-AMV in previously published papers, none showed specific descriptions of the drainage route to the brain stem [4,5,11]. In our review of cases of cavernous dural AVFs, we demonstrated a high incidence of cases of bridging venous drainage into the APM-AMV system (seven of 40 cases).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…To the best of our knowledge, only one case has been reported for the bridging venous drainage in the English literature [6]. Although we found some additional cases of angiography suggesting bridging venous drainage to the APM-AMV in previously published papers, none showed specific descriptions of the drainage route to the brain stem [4,5,11]. In our review of cases of cavernous dural AVFs, we demonstrated a high incidence of cases of bridging venous drainage into the APM-AMV system (seven of 40 cases).…”
Section: Discussionmentioning
confidence: 64%
“…All four cases of dural AVFs presented with subsrachnoid hemorrhage, and the AVFs drained ascending into the cavernous sinus, the superior petrosal sinus, or the inferior petrosal sinus. Several cases of intracranial dural AVFs draining into the APM-AMV system have been reported, and the majority of the reported cases showed brain stem injury due to venous congestion and/or hemorrhage [3][4][5][6]. Two potential drainage routes to the APM-AMV system of the petrosal venous route and the bridging venous routes exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulbar dysfunction was reported in seven cases. 22) The neurological symptoms of our patient were most likely related to spinal cord dysfunction (bowel and bladder dysfunction and paraparesis) as well as brainstem signs such as unconsciousness and dyspnea. The symptoms of our patient are similar to those of previously reported cases of intracranial dAVFs, in which the patients presented with myelopathy first and brainstem symptoms appeared later.…”
Section: Discussionmentioning
confidence: 73%
“…[2][3][4][6][7][8]10,[15][16][17][19][20][21][22][23][24][25][26][27][28][29][30] The most common symptom is ascending myelopathy, starting as loss of sensation and motor function in the lower extremities and extending to the upper extremities. Sphincter function is impaired.…”
Section: Discussionmentioning
confidence: 99%